2D Virtual Reality-Based Exercise Improves Spatial Navigation in Institutionalized Non-robust Older Persons: A Preliminary Data Report of a Single-Blind, Randomized, and Controlled Study - Oliveira, Luciana Mendes; Evangelista e Souza, Eric Hudson; Alves, Mariana Rocha; Carneiro, Lara S. F.; Fagundes, Daniel Ferreira; de Paula, Alfredo Maurício Batista; Engedal, Knut; Nascimento, Osvaldo J. M.; Monteiro-Junior, Renato Sobral (Frontiers in Neurology, 2021)
Background: Spatial navigation is a marker of prodromal dementia. Exercise with virtual reality improves cognitive functions but the effects on spatial navigation is unclear. Aim: We aimed at investigating the effect of virtual reality-based physical exercise with 2D exergames in spatial navigation in institutionalized non-robust elderly. Method: This study was registered in the Brazilian Registry of Clinical Trials (Protocol RBR-8dv3kg - http://www.ensaiosclinicos.gov.br/rg/RBR-6rytw2/). A total of 14 elderly (aged≧60) were randomly allocated to the exergames (EG) and active control (ACG) groups. EG performed exercises with 2D exergames, while ACG used the same movements as EG but without the use of virtual reality. Spatial navigation was assessed through Floor Maze Test. The immediate maze time (IMT) and delayed maze time (DMT) were recorded. Results: Spatial navigation enhanced in EG participants compared to ACG individuals. There was a significant (p=0.01) reduction between groups in the time to perform the IMT while the time in the DMT without prior planning showed a difference in the significance threshold (p=0.07). Conclusion: Virtual reality-based exercise improves spatial navigation of institutionalized non-robust elderly. This study should be replicated to confirm findings herein showed.